Produção e análise de mídias sobre o tema aquecimento global para a divulgação e o ensino de química - Pianheri, Anieli (2013)
The scientific concepts learning process associated to currently and relevant themes provides a better understanding by the individual, and especially by the students whose knowledge is associated to school program. Therefore, the pedagogical role development associated to high school chemical structures studies in school curriculum for science popularization in different kinds of media such as video, simulations, images and games becomes very important especially in places focusing non-formal and informal education, considering a large number of students and visitors of the science centers. In this sense, were developed and evaluated didactic-pedagogical chemical contents towards climate change into Complexo Integrado de Educação, Ciência e Cultura (CIECC) of São José do Rio Preto (SP), using qualitative research methodology. The medias produced fun shows and interactive / educational issue, through which visitors (especially students from public and private basic education) can reflect on human activities and their contributions as well as to know and discuss the role paper of chemistry in this issue, in addition to learning chemistry concepts using references such as virtual medias. The results obtained related to global warming concepts showed the student and visitor´s interests who claimed to be a properly way to promote scientific literacy.